Effects of Message Framing on Influenza Vaccination: Understanding the Role of Risk Disclosure, Perceived Vaccine Efficacy, and Felt Ambivalence. Issue 1 (2nd January 2019) - Kim, Sungsu; Pjesivac, Ivanka; Jin, Yan
ABSTRACT: The current study examined the effects of framing in promotional health messages on intention to vaccinate against seasonal influenza virus. The findings of an experimental study ( N  = 86) indicated that exposure to both benefits and side effects of vaccination (gain-framed with risk disclosure message) led to lower intention to receive the flu vaccine. This relationship was mediated by both perceived vaccine efficacy and felt ambivalence in a serial order, revealing the underlying psychological mechanisms important for understanding health-related behaviors. Theoretical implications of constructing sub-framed messages are discussed and the concept of second-order framing is introduced.